Effect of Planting Patterns on the Growth, Development, and Productivity of Vegetable Bean - Sanayev, S. T.; Khudayqulova, M. Sh. (American Journal of Botany and Bioengineering, 2025)
The article presents experimental data on the growth and development of vegetable bean (Phaseolus vulgaris L.) cultivars Ravot and Mahsuldor grown under different planting patterns (plant densities). The study reports variations in plant height (50.4–68.8 cm), number of lateral branches (3.2–6.7), number of leaves (36.1–69.3), shoot biomass (170.1–356.2 g), leaf biomass (54.2–74.5 g), root biomass (7.3–13.8 g), and green pod yield (8.4–14.9 t/ha).